2012
DOI: 10.3182/20120829-3-mx-2028.00165
|View full text |Cite
|
Sign up to set email alerts
|

Features Selection Procedure for Prognostics: An Approach Based on Predictability

Abstract: Prognostic aims at estimating the remaining useful life (RU L) of a degrading equipment, i.e at predicting the life time at which a component or a system will be unable to perform a desired function. This task is achieved through essential steps of data acquisition, feature extraction and selection, and prognostic modeling. This paper emphasizes on the selection phase and aims at showing that it should be performed according to the predictability of features: as there is no interest in retaining features that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…For complex systems under dynamic regimes, the use of neural networks for RUL estimation is extended for higher performance levels of the learning methodology [95,96]. Particularly, the feature selection procedure is applied within the he neural network based prognostics and it is shown that it should be performed according to the predictability of features [97]. For multi-step estimations, the network structures such as non-linear autoregressive ANN models form dynamic filtering frameworks in which past monitoring information is used to predict the future values [98].…”
Section: Artificial Neural Network and Deep Learningmentioning
confidence: 99%
“…For complex systems under dynamic regimes, the use of neural networks for RUL estimation is extended for higher performance levels of the learning methodology [95,96]. Particularly, the feature selection procedure is applied within the he neural network based prognostics and it is shown that it should be performed according to the predictability of features [97]. For multi-step estimations, the network structures such as non-linear autoregressive ANN models form dynamic filtering frameworks in which past monitoring information is used to predict the future values [98].…”
Section: Artificial Neural Network and Deep Learningmentioning
confidence: 99%
“…Describing the problem of prognostics by means of continuous predictions and discrete state estimations is new in PHM community and its only addressed in few publications [14], [16], [18]. Obviously, for prognostics part, the prediction phase is critical and must be dealt in an accurate manner for timely decisions.…”
Section: Enhanced Multivariate Prognostics Modelingmentioning
confidence: 99%
“…divided a degradation feature into segments and the average separability of all segments was defined for feature selection, and optimal degenerative features were outstood. Predictability accounts for prediction horizon, tolerate accuracy and prognostic model error was formulated by Javed et al . for prognostic feature selection.…”
Section: Introductionmentioning
confidence: 99%
“…Camci et al 26 divided a degradation feature into segments and the average separability of all segments was defined for feature selection, and optimal degenerative features were outstood. Predictability accounts for prediction horizon, tolerate accuracy and prognostic model error was formulated by Javed et al 27 for prognostic feature selection. Although feature evaluation for diagnostics has been much studied with indices based on intraclass closeness and interclass separability, it is not trivial to define goodness metrics for prognostic feature evaluation and selection.…”
Section: Introductionmentioning
confidence: 99%